Strategi Program Eco-School Dalam Menghadirkan Karakter Peduli Lingkungan - Karmilasari, Vina; Putri, Devi Sutrisno; Faedlulloh, Dodi (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2020)
The phenomenon of natural disasters that has come and gone recently has jolted our minds and made us think backward to relate these incidents to the educational process that has been applied. Eco-school is a large program that accommodates the desire of schools to play a role in preserving the environment. Eco-school programs combine learning and action, making them an effective method for changing behavior and shaping character. Law Number 20 of 2003 concerning the National education system and Presidential Regulation Number 87 of 2017 concerning Strengthening Character Education emphasize the importance of carrying out a national character revolution. The Character Education Strengthening Program (PPK) is in line with the Nawacita agenda of strengthening the character of the nation through character and character building of students as part of the mental revolution. In the National Long-Term Development Plan Rencana Pembangunan Jangka Panjang Nasional (RPJPN) 2005-2025, the Government implicitly emphasized that character development is one of the priority programs of national development. To be able to achieve the maximum target from implementing eco-school, an appropriate and capable strategy is needed in executing all these programs. Prioritizing the process of deep communication interaction between the researcher and the phenomenon under study, the strategy model that will be formulated through this research is expected to contribute to shaping the character of students who care about the environment which then simultaneously supports the achievement of sustainable development goals through the character of caring for the environment.